Dendritic cell maturation and cross-presentation: timing matters! - Alloatti, Andrés (2016)
As a population, dendritic cells (DCs) appear to be the best cross-presenters of internalized antigens on major histocompatibility complex class I molecules in the mouse. To do this, DCs have developed a number of unique and dedicated means to control their endocytic and phagocytic pathways: among them, the capacity to limit acidification of their phagosomes, to prevent proteolytic degradation, to delay fusion of phagosomes to lysosomes, to recruit ER proteins to phagosomes, and to export phagocytosed antigens to the cytosol. The regulation of phagocytic functions, and thereby of antigen processing and presentation by innate signaling, represents a critical level of integration of adaptive and innate immune responses. Understanding how innate signals control antigen cross-presentation is critical to define effective vaccination strategies for CD8+ T-cell responses.